PERAN LOCUS OF CONTROL PADA HUBUNGAN JOB INSECURITY, KOMITMEN DAN KEPUASAN KERJA - Retno Sari, Santi; Thawil, Sitti Marijam (Economic Faculty, Attahiriyah Islamic University, 2016)
The purpose of this paper is to examine the relationships between job insecurity and its outcomes (job satisfaction and commitment), also to examine the moderator role of locus of control in this relationship. Data were collected from 143 employees across different industries, and also different job levels. A series of regressions are employed to test the hypotheses. The results showed that job insecurity was directly and negatively related to job satisfaction and organizational commitment. The research findings also showed that locus of control moderated relations between job insecurity and two studied outcomes (job satisfaction and commitment). This study offers implications for managerial practices. This result suggest for manager how to overcome the impact of job insecurity on commitment and job satisfaction through locus of control. Keywords: job insecurity, locus of control, job satisfaction, commitment